Private Equity focused on Family Firms & Small and Medium Sized Companies: Review and Science Mapping Analysis of the Recent Scientific Field - Arteche-Bueno, Laura; Prado-Román, Camilo; Fernández-Portillo, Antonio (European Journal of Family Business, 2019)
Private equity is mostly invested in established firms, of which family firms are the dominant form. This article reports the recent evolution of the scientific research on the PE focused on family firms and small and medium-sized enterprises. The purpose is to identify the main themes related to the field between 1992 and 2018 and to identify and analyze the major thematic areas throughout the period. The methodology applied is the science mapping analysis, which shows that: (i) published research on the field is concentrated in two main thematic areas: corporate governance-entrepreneurship and innovation-management, and; (ii) there has been an atomization of the research field during the last six years. Throughout this article, the authors develop a more complete understanding of the PE scientific field focused on family owned SMEs and provide suggestions for those looking for alternatives to traditional bank financing.